2020
DOI: 10.1002/humu.24001
|View full text |Cite
|
Sign up to set email alerts
|

ZMYND11 ‐related syndromic intellectual disability: 16 patients delineating and expanding the phenotypic spectrum

Abstract: Pathogenic variants in ZMYND11, which acts as a transcriptional repressor, have been associated with intellectual disability, behavioral abnormalities, and seizures.Only 11 affected individuals have been reported to date, and the phenotype associated with pathogenic variants in this gene have not been fully defined. Here, we present 16 additional patients with predicted pathogenic heterozygous variants in including four individuals from the same family, to further delineate and expand the genotypic and phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Less frequent associations included micro‐ or macrocephaly, visual or hearing impairment. A broad but variable pattern of dysmorphism consistent with that already described 14 was present in only 12 individuals (Table 1) with some additional, previously unreported features including modified palmar crease, bushy eyebrows, thick digits and hypoplastic teeth (one individual each); the remaining eight individuals had no discernible facial dysmorphism. Neuroimaging findings revealed either no abnormalities or nonspecific features: prenatal infarct, ventricular enlargement/cerebral atrophy, delayed myelination, Chiari I abnormality (n = 2), glial scar; one individual had posterior polymicrogyria.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Less frequent associations included micro‐ or macrocephaly, visual or hearing impairment. A broad but variable pattern of dysmorphism consistent with that already described 14 was present in only 12 individuals (Table 1) with some additional, previously unreported features including modified palmar crease, bushy eyebrows, thick digits and hypoplastic teeth (one individual each); the remaining eight individuals had no discernible facial dysmorphism. Neuroimaging findings revealed either no abnormalities or nonspecific features: prenatal infarct, ventricular enlargement/cerebral atrophy, delayed myelination, Chiari I abnormality (n = 2), glial scar; one individual had posterior polymicrogyria.…”
Section: Resultssupporting
confidence: 71%
“…We identified individuals from Gene Matcher, 15 PubMed 6,8,14,16 the European Network Therapy Rare Epilepsies (NETRE), 17 and ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/), and the clinical information was systematically summarised by local clinicians. All individuals were tested using currently available next generation sequencing technology, either through whole exome sequencing or gene panels for neurodevelopmental disorders, 18 a few also with mitochondrial genome sequencing and deletion analysis (#2, #12, #16) 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumiene et al suggested that the clinical features of 10p15.3 microdeletion included neurodevelopmental disorders, characteristic dysmorphic features, and some other more frequent symptoms, and that the ZMYND11 gene was responsible for the above phenotype (24). As a transcriptional repressor, mutations of ZMYND11 have been associated with autosomal dominant mental retardation type 30 leading to intellectual disability, behavioral abnormalities, and seizures (25). Pathogenic single nucleotide variants (SNVs) of ZMYND11 were also associated with Cornelia de Lange syndrome in a large study (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ZMYND11 variants were identified in mice with anxiety-like behavior (Parker et al, 2016). Pathogenic variants in ZMYND11 have been associated with intellectual disability, behavioral abnormalities, and seizures in humans (Yates et al, 2020).…”
Section: Selection Signature Genes Of the Chongming White Goat Breedmentioning
confidence: 99%